GdVO4:Eu3+ and LaVO4:Eu3+ Nanoparticles Exacerbate Oxidative Stress in L929 Cells: Potential Implications for Cancer Therapy - Kot, Yuriy; Klochkov, Vladimir; Prokopiuk, Volodymyr; Sedyh, Olha; Tryfonyuk, Liliya; Grygorova, Ganna; Karpenko, Nina; Tomchuk, Oleksandr; Kot, Kateryna; Onishchenko, Anatolii; Yefimova, Svetlana; Tkachenko, Anton (International journal of molecular sciences, 2024)
The therapeutic potential of redox-active nanoscale materials as antioxidant- or reactive oxygen species (ROS)-inducing agents was intensely studied. Herein, we demonstrate that the synthesized and characterized GdVO4:Eu3+ and LaVO4:Eu3+ nanoparticles, which have been already shown to have redox-active, anti-inflammatory, antibacterial, and wound healing properties, both in vitro and in vivo, worsen oxidative stress of L929 cells triggered by hydrogen peroxide or tert-butyl hydroperoxide (tBuOOH) at the concentrations that are safe for intact L929 cells. This effect was observed upon internalization of the investigated nanosized materials and is associated with the cleavage of caspase-3 and caspase-9 without recruitment of caspase-8. Such changes in the caspase cascade indicate activation of the intrinsic caspase-9-dependent mitochondrial but not the extrinsic death, receptor-mediated, and caspase-8-dependent apoptotic pathway. The GdVO4:Eu3+ and LaVO4:Eu3+ nanoparticle-induced apoptosis of oxidatively compromised L929 cells is mediated by ROS overgeneration, Ca2+ overload, endoplasmic reticulum stress-associated JNK (c-Jun N-terminal kinase), and DNA damage-inducible transcript 3 (DDIT3). Our findings demonstrate that GdVO4:Eu3+ and LaVO4:Eu3+ nanoparticles aggravate the oxidative stress-induced damage to L929 cells, indicating that they might potentially be applied as anti-cancer agents.
Keywords: nanoparticles; oxidační stres; Cell Line; Neoplasms; reaktivní formy kyslíku; Nanoparticles; gadolinium; nanočástice; oxidative stress; peroxid vodíku; Hydrogen Peroxide; caspase; stres endoplazmatického retikula; Reactive Oxygen Species; kovové nanočástice; intrinsic apoptosis; Animals; Metal Nanoparticles; zvířata; Gadolinium; myši; apoptóza; buněčné linie; apoptosis; nádory; Endoplasmic Reticulum Stress; nanotoxicity; Mice; Oxidative Stress; Apoptosis